Objectification of the Lite and Darkness archetypes in the structure of the semantic field of «heart» in the Ukrainian poetic discourse of the XIX century (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The peculiarities of the Lite and Darkness archetypes linguistic materialization in the structure of the semantic field of «heart» in the Ukrainian poetic discourse of the XIX century were analyzed in the article. Conceptual-semantic organization of the lexical field, which the Lite and Darkness archetypes had been underlain, was described. The place of this microfield in the structure of the thematic field of «heart» in the Ukrainian poetry of the XIX century was determined.
Keywords: archetype; lexical-semantic field; language image